2015
DOI: 10.1111/ejh.12605
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric measurement of platelet‐associated immunoglobulin in children with newly diagnosed Immune Thrombocytopenia

Abstract: Approximately one-quarter of children are PAIG-negative, and these children have milder bleeding tendency at diagnosis and lower morbidity during follow-up. Raised PAIG possibly may cause some degree of platelet dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
1
9
1
Order By: Relevance
“…Moreover, sensitivity was the same for newly diagnosed, as well as chronic ITP, and for glycoprotein‐specific assays . The results were unchanged when only the largest studies were considered .…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, sensitivity was the same for newly diagnosed, as well as chronic ITP, and for glycoprotein‐specific assays . The results were unchanged when only the largest studies were considered .…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, when measuring antibodies at diagnosis, Fu et al found that patients with a prognosis of chronic ITP showed enrichment of anti‐GP Ib/IX antibodies, compared to those with transient disease courses (N = 18 vs. N = 113) . Findings of these two studies are contrasted by Biglino et al who observed equal rates of anti‐GPIIb/IIIa or anti‐GPIb/IX antibodies in patients with transient or chronic disease courses (N = 49 vs. N = 25) and Nielsen et al who showed a similar rate of anti‐platelet antibodies by PA‐IgG/IgM amongst patients with transient and chronic diseases courses (N = 46 vs. N = 12). Taken together, some studies indicate a role of anti‐platelet antibody testing to determine prognosis, but in the presence of conflicting evidence further data are required.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now known that multiple platelet glycoproteins can be involved, including GP V and the GP Ib/IX complex . In childhood ITP, IgM anti‐platelet antibodies have been suggested to be at least as prevalent as anti‐platelet IgG antibodies . Apart from affecting platelet clearance, anti‐glycoprotein antibodies can functionally impair platelet aggregation by blocking the fibrinogen receptor interactions, or may potentially inhibit effective thrombopoiesis through GPIbα‐mediated hepatocyte thrombopoietin production …”
Section: Introductionmentioning
confidence: 99%